The impact of the financial and economic crisis on world trade and trade policy - Louise Curran; Hubert Escaith; Jean-Jacques Hallaert; Claude Barfield; Simon J. Evenett; Georg Koopmann (Intereconomics, 2009)
This Forum is dedicated to a discussion of the effects of the global financial and economic crisis on both international trade and trade policy. What changes could be observed in the volume and structure of trade and what transmission channels were involved? Has the international competitiveness of the European Union and its member countries been affected? What has been the impact of the crisis on trade policy? Are the widespread fears of a revival of protectionism justified? How can trade policy help to overcome the crisis?
Keywords: 330